Mountain hiking in the Stołowe Mountains National Park - Mateusz Rogowski (Tourism, 2017)
In recent years the Stołowe Mountains National Park has become an increasingly popular destination for the purposes of mountain tourism. Such tourism takes different forms throughout the year, but the most common is hiking. Its continuing popularity results from the close contact with nature it provides, along with the possibility of active leisure pursuits and exploration. The aim of the study is to describe the motivations, preferences and leisure behaviours of hiking tourists who visit the Stołowe Mountains National Park, through survey-based research in 2015 and 2016. The study will highlight the relationship between the respondents’ characteristics and their motivations, preferences and behaviour, to identify the main kinds of tourists.